2021
DOI: 10.1108/jfra-08-2020-0249
|View full text |Cite
|
Sign up to set email alerts
|

Do firm characteristics and ownership structure affect corporate philanthropic contributions in Jordan?

Abstract: Purpose This paper aims to examine the drivers of corporate donations in Jordan. In particular, to examine whether firm-specific characteristics and ownership types affect corporate donations. Design/methodology/approach The analysis is based on a sample of 94 Jordanian listed companies, drawn from the manufacturing and service sectors, over the period 2010–2016. This paper uses ordinary least square regression with a year and industry fixed effects to test the research hypotheses. Findings This paper find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
65
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 38 publications
(65 citation statements)
references
References 80 publications
0
65
0
Order By: Relevance
“…Also, family-owned companies are highly prevalent (Abdullatif et al , 2019). In such a setting, family ties tend to influence the appointment of board directors, making it inherently difficult to attain higher transparency due to the low level of board independence (Ananzeh et al , 2021). Moreover, the same holds true for female directors who would be elected based upon family ties to ensure more support for most of management decisions (Ahmad et al , 2018).…”
Section: Institutional Context Of Jordanmentioning
confidence: 99%
“…Also, family-owned companies are highly prevalent (Abdullatif et al , 2019). In such a setting, family ties tend to influence the appointment of board directors, making it inherently difficult to attain higher transparency due to the low level of board independence (Ananzeh et al , 2021). Moreover, the same holds true for female directors who would be elected based upon family ties to ensure more support for most of management decisions (Ahmad et al , 2018).…”
Section: Institutional Context Of Jordanmentioning
confidence: 99%
“…This issue has sparked debate in the literature and is still vital in the business arena. Profitable businesses generate value, employ employees, and strive to be more creative and appealing to potential and current investors (Odusanya et al, 2018;Ananzeh et al, 2021). The importance of this study stems from identifying the internal determinants affecting a firm's profitability and how to develop it.…”
Section: Introductionmentioning
confidence: 99%
“…Although the concept of CSR has been analyzed in depth in Western countries, there is a dearth of empirical research in developing nations like the MENA region [34]. One of the latest studies examined the determining factors of CSR in 94 Jordanian companies from the manufacturing and service industries [35]. Their findings revealed that (a) company maturity, profitability, and size have positive impacts on CSR participation; (b) a high percentage of debt to assets is a barrier to Jordanian companies' participation in socially responsible activities; (c) family-owned companies have less incentive to engage in CSR activities; and (d) low concentrated ownership and media coverage are also accounted for as drivers of CSR engagement.…”
Section: Middle East and North Africa (Mena)mentioning
confidence: 99%